Byod practices in Malaysia public sector - Jusoh, Mohd Yusri; Haron, Haryani; Kaur, Jasber (2016)
Bring your own Device (BYOD) is currently heighted as an approach towards green computing. With the current usage of mobile devices such as the smart phones, tablets, and laptops as the necessity in the working environment, the concept of BYOD went beyond personal use towards workplace.This study explores the BYOD practices in public sector in relation to the green initiatives.Qualitative research approach is used in the study with the main data collection method of interviews and document analysis.The study discovered two models of BYOD approach in the Malaysian public sector, which are the personally owned devices model and the organization owned devices model.